Type 2 diabetes mellitus patients' satisfaction with pharmacy services in Wollega University Referral Hospital, Western Ethiopia. Issue 6 (22nd November 2020) - Fekadu, Ginenus; Dereje, Saktu; Dugassa, Dinka; Bekele, Firomsa; Simegnew, Dawit; Turi, Ebisa; Tolossa, Tadesse; Fetensa, Getahun; Alemu, Tamirat; Gamachu, Busha
Abstract : Introduction: Ensuring the quality of pharmaceutical services in hospitals is an integral aspect of providing quality of health care. In this regard, it has long been proven that the adoption of the concept of pharmaceutical care is essential to improve the quality of pharmaceutical services. Hence, this study aimed to assess type 2 diabetes mellitus patients' satisfaction with pharmacy services in Wollega University Referral Hospital, West Ethiopia. Methods: Descriptive cross-sectional study design was employed from May to June 2019. Data were collected using both close and open-ended questionnaires from the sample of type 2 diabetes mellitus patients. The collected data were analyzed using Statistical Package for Social Science version 20 and Descriptive data were explained by frequency and percentage. Results: From a total of 195 study participants, 124 (64%) were satisfied with pharmacy service. Patients who were satisfied with pharmacy services reported possible reasons like availability of the prescribed drugs, affordability, and notice of information on the drug package that is not taken with foods. However, patients were dissatisfied with other pharmacy related factors like the reflection of negative attitude from the pharmacists and withholding information on what to do during the occurrences of adverse effects. About two thirds (67.8%) patients agreed with the availability of prescribed medicines. None of the patients had negative attitude toward the pharmacists. About 43.1% of the patients strongly disagreed with unclear instruction of taking medicines. Conclusion: The patients' satisfaction level with pharmacy service was affected by different pharmacy service-related factors. The management of Wollega University Referral Hospital has to establish and activate information centers to sufficiently provide drug information for the patients and motivate pharmacists morally and financially.